Tubeimoside-1: A review of its antitumor effects, pharmacokinetics, toxicity, and targeting preparations - Wang, Chang-Lin; Gao, Ming-Zhou; Gao, Dong-Mei; Guo, Ying-Hui; Gao, Zhan; Gao, Xiang-Ju; Wang, Jie-Qiong; Qiao, Ming-Qi (Frontiers in Pharmacology, 2022)
Tubeimoside-1 (TBMS-1), a natural triterpenoid saponin found in traditional Chinese herbal medicine Bolbostemmatis Rhizoma, is present in numerous Chinese medicine preparations. This review aims to comprehensively describe the pharmacology, pharmacokinetics, toxicity and targeting preparations of TBMS-1, as well the therapeutic potential for cancer treatement. Information concerning TBMS-1 was systematically collected from the authoritative internet database of PubMed, Web of Science, and China National Knowledge Infrastructure applying a combination of keywords involving “tumor”, “pharmacokinetics”, “toxicology” and targeting preparations. New evidence shows that TBMS-1 possesses a remarkable inhibitory effect on the tumors of the respiratory system, digestive system, nervous system, genital system as well as other systems in vivo and in vitro. Pharmacokinetic studies reveal that TBMS-1 is extensively distributed in various tissues and prone to degradation by the gastrointestinal tract after oral administration, causing a decrease in bioavailability. Meanwhile, several lines of evidence have shown that TBMS-1 may cause adverse and toxic effects at high doses. The development of liver-targeting and lung-targeting preparations can reduce the toxic effect of TBMS-1 and increase its efficacy. In summary, TBMS-1 can effectively control tumor treatment. However, additional research is necessary to investigate in vivo antitumor effects and the pharmacokinetics of TBMS-1. In addition, to reduce the toxicity of TBMS-1, future research should aim to modify its structure, formulate targeting preparations or combinations with other drugs.